School science for six year olds: a neo-vygotskian approach to curriculum analysis - Morris, Anya Caroline (School of Education, 2014)
The purpose of this study is to describe the form of knowledge that is made available to six year olds as 'Science' in key South African Grade R curriculum texts. The study draws on a neo-Vygotskian conceptualisation of forms of knowledge and child development to develop a language of description in terms of which the selected texts are analysed. Representations of knowledge in the curriculum texts are described in relation to the notion of a simple scientific concept, an idea that was derived from a neo-Vygotskian conceptualisation of knowledge. A simple scientific concept is consistent with scientific criteria and functions as an entry level concept in relation to scientific knowledge. Findings indicate that the Grade R science curriculum represents knowledge in terms of everyday concepts and 'potential' scientific concepts, i.e. concepts that have the potential to prompt the Grade R educator to translate an everyday concept into a simple scientific concept. However, the curriculum does not represent any concepts in ways that conform to the criteria for scientific concepts, including simple scientific concepts. The study concludes that the official recontextualisation of scientific knowledge into Grade R school science is problematic because the Grade R science curriculum represents knowledge mostly in everyday terms. The implications are that Grade R learners are not given the opportunity to acquire the form or content of scientific knowledge or to develop the cognitive skills required for formal schooling.